Peran Literasi Keuangan Sebagai Pemoderasi Persepsi Kemudahan dan Persepsi Risiko Terhadap Minat Penggunaan Aplikasi Pencatatan Laporan Keuangan Pada Sektor UMKM (Studi pada UMKM Konveksi di Kecamatan Comal) - Faradiba, Aldilase Adib; Lukiastuti, Fitri; Puryandani, Siti; Pujiastuti, Yanti (Magister Manajemen STIE Bank BPD Jateng, 2025)
This study aims to determine the role of financial literacy as a moderator of perceived ease and perceived risk on the interest in using financial reporting applications in the MSME sector. This study uses a quantitative approach with data collection techniques through questionnaires and involves 80 respondents. The population in this study were MSME Convection Actors in Comal District. The analysis technique used in this study is SEM (Structural Equation Model) using Smart Partial Least Square (SmartPLS) 4.0 software. The results of this study indicate that perceived ease has a negative and insignificant effect on the interest in using financial reporting applications for MSME Convection in Comal District, and perceived risk has a positive and significant effect on the interest in using financial reporting applications for MSME Convection in Comal District. Meanwhile, the role of financial literacy cannot moderate the effect of perceived ease on the interest in using financial reporting applications for MSME Convection in Comal District, and financialliteracy can moderate the perception of risk on the interest in using financial reporting applications for MSME Convection in Comal District.